2012
DOI: 10.4304/jcp.7.11.2773-2780
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Real-time Fault-tolerant Scheduling Algorithm for Partial Reconfigurable System

Abstract: Partial reconfigurable system is an architecture consisting general purpose processors and FPGAs, in which FPGA can be reconfigured in run-time. Based on the architecture, software tasks and hardware tasks that are executed on processor and FPGA respectively co-exist. In this paper, a real-time fault-tolerant scheduling algorithm is proposed to schedule software/hardware hybrid tasks. In the algorithm, the sufficient condition for schedulable hybrid tasks is derived from analyzing system operation conditions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…For example, a Primary/Backup scheme is proposed in [35] in which two versions of a task run with minimum time overlap. In [36], a real-time fault-tolerant scheduling algorithm is proposed which, schedules hybrid tasks able to tolerate f i faults during task execution. Our previous study [6] showed that, by using optimization methods and choosing, for each task, the proper FT technique from the Pareto-set (referred to as Pareto-based FT techniques), it is possible to increase the reliability of task graphs without deteriorating their makespan.…”
Section: Related Workmentioning
confidence: 99%
“…For example, a Primary/Backup scheme is proposed in [35] in which two versions of a task run with minimum time overlap. In [36], a real-time fault-tolerant scheduling algorithm is proposed which, schedules hybrid tasks able to tolerate f i faults during task execution. Our previous study [6] showed that, by using optimization methods and choosing, for each task, the proper FT technique from the Pareto-set (referred to as Pareto-based FT techniques), it is possible to increase the reliability of task graphs without deteriorating their makespan.…”
Section: Related Workmentioning
confidence: 99%
“…Several hybrid algorithms, which combine EDF with conventional disk scheduling algorithms, are proposed in recent years [17] [18] [19]. FD-EDF (Feasible Deadline EDF) serves requests using the EDF algorithm if there are requests with feasible deadlines in the waiting queue; otherwise, it serves the queue using FCFS.…”
Section: The Traditional I/o Scheduling Algorithmsmentioning
confidence: 99%
“…Through the above analysis of the simulation experiment results we can conclude that HB-SCHED algorithm has a better real-time performance than SCAN and a better throughput performance than EDF. And take "a = 0.6" for example, figure 6 shows the experiment results of J(X) defined in (17) , which is the single objective optimization target of HB-SCHED. We can see that HB-SCHED is higher than EDF and SCAN.…”
Section: Simulation and Analysismentioning
confidence: 99%
“…(12) and Eq. (17) have been used to obtain the MTTF and the makespan of the task graph, respectively.…”
Section: Motivational Examplementioning
confidence: 99%
“…For instance, a Primary/Backup scheme is proposed in [16] in order to support FT while scheduling. In [17], a realtime fault-tolerant scheduling algorithm is presented so that, by using a sufficient schedulability test condition, it schedules hybrid hardware/software tasks that are able to tolerate f i faults during task execution. Recently, we have investigated the application of different FT strategies on different real-time scheduling algorithms in reconfigurable platforms [18].…”
mentioning
confidence: 99%